Intestinal Obstruction of Uncommon Cause and Point-of-Care Ultrasonography: Where Do We Stand - Capela,Tiago (2018)
Malignant neoplasms of the small bowel, especially from the jejunum, are among the rarest types of cancer. Given its location, a delayed diagnosis is frequent and sometimes only made in an emergency context. The authors present a case of intestinal obstruction, where ultrasonography was pivotal in establishing a diagnosis. Point-of-care ultrasonography seems to be particularly sensitive in assessing emergency patients with abdominal pain, allowing effective orientation and saving human and technical resources.